HUBUNGAN EXPLOSIVE POWER OTO LENGAN DAN BAHU DENGAN HASIL TOLAK PELURU SISWA KELAS VII SMPN 05 TELUK KUANTAN KECAMATAN KUANTAN TENGAH - Gusmardi '; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of this study originated from the observation while at SMPN 05 Teluk Kuantan, it was found that the results of shot put students are still in the poor category. This is presumably due to a physical condition that is explosive power arm and shoulder muscles. So the purpose of this study was to determine whether there is a corelation of explosive power arm and shoulder muscles with the shot put results of Class VII student of SMP N 05 Teluk Kuantan District of Kuantan Tengah. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. Sampling in this study using total sampling so that the sample in this study amounted to 14 male students. The data in this study was obtained from the results of the test measurements two hand medicine ball put and shot put. Based on the research that has been done in Class VII SMP N 05 Teluk Kuantan District of Kuantan Tengah obtained r = 0.697 medium category. Tests of significance using the formula Significance t distribution. From the calculation results are known t = 3,36, while t table = 1.782 so t = 3.36> t table = 1.782. Then it can be concluded as follows: There is a significant corelation between the explosive power arm muscles on the ability of shot put by category enough because r = 0.697 in Class VII SMP N 05 Teluk Kuantan District of Kuantan Tengah.Keywords : Explosive Power, Arm Muscle, Shot Put